Предмет: Алгебра,
автор: Vetaskyy
(x-3)^2-(x-3)(x+3)=0
Ответы
Автор ответа:
0
(x-3)^2-(x^2-3^2)=0
(x-3)^2-(x^2-9)=0
(x-3)^2-x^2+9=0
x^2-6x+9-x^2=-9
-6x+9=-9
-6x=-9-9
-6x=-18
6x=18
x=3
(x-3)^2-(x^2-9)=0
(x-3)^2-x^2+9=0
x^2-6x+9-x^2=-9
-6x+9=-9
-6x=-9-9
-6x=-18
6x=18
x=3
Автор ответа:
0
пожалуйста)
Автор ответа:
0
зачем так запутано
Похожие вопросы
Предмет: Английский язык,
автор: natashasklema1985
Предмет: Физика,
автор: LadyBlackCat
Предмет: Геометрия,
автор: paralperson
Предмет: Математика,
автор: kazakovatanya6